Adsorption of Rare Earth Metals from Water using a Kenaf Cellulose-based Poly(hydroxamic acid) Ligand - Lutfor, M. R.; Biswas, Tapan Kumar; Sarkar, Shaheen M.; M. M., Yusoff; Mohd Sani, Sarjadi; Arshad, Sazmal E.; Musta, Baba (Elsevier, 2017)
A kenaf cellulose-based poly(hydroxamic acid) ligandwas synthesized frompoly(methylacrylate) grafted cellulose and applied towards the adsorption of rare earthmetals fromaqueousmedia. The startingmaterials and final product were examined by FT-IR, FE-SEM, and ICP-MS. Remarkable maximum adsorption results were obtained for the earthmetals La3+, Ce3+, Pr3+, Gd3+, Nd3+, Eu3+, and Sm3+, with values of 260, 245, 235, 220, 210, 195, and 192 mg g−1, respectively. The adsorption capacities of the ligand for adsorption of rare earth metals were well fitted with the pseudo-second-order rate equation. Further, the adsorption properties of the rare earth ionswere nicelymatchedwith the Langmuir isothermmodel, (R2 N 0.99), thus suggesting that the adsorbent surface of the ligand ismonolayer and homogenous in nature. The reusability of the created ligandwas evaluated by carrying out sequential sorption/desorption experiments, indicating that the developed adsorbent can be reused for at least 10 cycles without incurring any significant losses to its primary removal capabilities.